Ground ants as indicators of biodiversity in cashew agroecosystems in Tanzania - Moses I. Olotu (Bulletin of the National Research Centre)
Abstract Background Ants are a diverse and ecologically important group of insects that play vital roles in terrestrial ecosystems globally. In agricultural settings, they act as effective biocontrol agents against insect pests. Ants also serve as bioindicators of environmental health, reflecting changes in habitat and pollution. However, research on their diversity and population dynamics in cashew agroecosystems remains limited. Results The sampling was conducted using a pitfall trap that targeted three sampling zones viz., under African weaver ants colonised (AWAC) cashew trees, AWA-uncolonised (AWAUC) ones, and buffer zones (BZ). A total of 14,004 ants from six subfamilies, 18 genera, and 32 species were sampled, with 7,686 sampled during season one and 630 sampled during season two. The study found significant differences in ant populations across sampled zones, which were significantly different in season one (F(2.107) = 5.4; P = 0.01) and season two (F(2.107) = 3.32; P = 0.04). However, more ants were sampled under AWAUC cashew trees compared to AWAC cashew trees and the BZ (F(2.74) = 4.46; P = 0.02) at Nyamato during season one. The Shannon–Wiener diversity index yielded comparable results to Margalef’s species richness index for all three zones, which differed significantly in both seasons at Nyamato and season one at Chambezi. A SIMPER analysis showed an overall dissimilarity of 94.5% at Soga due to the presence of invasive species (Pheidole megacephala and Anoplolepis custodiens) and AWA, which was consistently observed across all the experimental sites. Conclusion The variety and number of ant species in cashew agroecosystems are influenced by several factors, including the presence of dominant ant species and weeding practices. Promoting biodiversity in agricultural ecosystems is crucial for supporting beneficial insect populations and mitigating the risks posed by invasive ant species. Currently, there is no effective bait available for controlling these invasive ant species, indicating a need for further research to develop such bait. This would facilitate the foraging activities of other ant species, including beneficial ones.